"With a little help from my friends": the evolving nature of friendship in the long sixties. Issue 1 (2nd January 2021) - Kutulas, Judy
ABSTRACT: After the revolutions of the Sixties, members of the Baby Boom generation (those born between 1946 and 1963) jumbled the categories of friends, lovers, and family, seeking the intimacy and support their parents found from partners in friends. How and why they built friendships and how those friendships differed from previous social understandings of friendships is the subject of this essay.